English-Indonesian Translation Methods in the Story of “Malin Kundang” - Algrin Hayadi; Ira Maisarah; Seth Soy (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
Abstract This research contains an analysis of the methods in translation used in the short story